Phytophthora parasitica transcriptome, a new concept in the understanding of the citrus gummosis - Rosa, Daniel D. [UNESP]; Campos, Magnólia A.; Targon, Maria Luisa P.N.; Souza, Alessandra A. (Sociedade Brasileira de Genética, 2007)
Due to the economic importance of gummosis disease for the citriculture, studies on P. parasitica-Citrus interaction comprise a significant part in the Brazilian Citrus genome data bank (CitEST). Among them, two cDNA libraries constructed from two different growth conditions of the P. parasitica pathogen are included which has generated the PP/CitEST database (CitEST - Center APTA Citros Sylvio Moreira/IAC- Millennium Institute). Through this genomic approach and clustering analyses the following has been observed: out of a total of 13,285 available in the Phytophthora parasitica database, a group of 4,567 clusters was formed, comprising 2,649 singlets and 1,918 contigs. Out of a total of 4,567 possible genes, only 2,651 clusters were categorized; among them, only 4.3% shared sequence similarities with pathogenicity factors and defense. Some of these possible genes (103) corresponding to 421 ESTs, were characterized by phylogenetic analysis and discussed. A comparison made with the COGEME database has shown homology which may be part of an evolutionary pathogenicity pathway present in Phytophthora and also in other fungi. Many of the genes which were identified here, which may encode proteins associated to mechanisms of citrus gummosis pathogenicity, represent only one facet of the pathogen-host Phytophthora - Citrus interaction.
Keywords: Citrus disease; elicitins; plant pathogen; gene expression profiles